Anti-obesity pharmacotherapy for treatment of pediatric type 2 diabetes: Review of the literature and lessons learned from adults - Bensignor, Megan O.; Kelly, Aaron S.; Arslanian, Silva (Frontiers in Endocrinology, 2022)
Type 2 diabetes mellitus (T2DM) in adolescents is a more rapidly progressive disease, associated with earlier and higher rates of microvascular complications than in adults. As obesity is a significant risk factor for T2DM development and progression, the American Diabetes Association (ADA) recommends anti-obesity medications (AOMs) as adjuvant therapy for adults with both T2DM and overweight/obesity. In adults, the addition of AOMs to a diabetes regimen can improve glycemic control, reduce weight, and decrease anti-diabetes medication use. The ADA recommends considering bariatric surgery for adolescents with T2DM who have a BMI >35 kg/m2, but did not mention the use of AOMs in their 2022 updated guidelines. Currently, there are three FDA-approved AOMs available for chronic use in adolescents with obesity. Other medications are used in an “off-label” fashion for appetite suppression and BMI reduction. As additional AOMs are being developed and FDA-approved for the pediatric population, new treatment options with novel mechanisms of action will become available for adolescents with T2DM and obesity. In this review, we will discuss the evidence for the use of AOMs in the treatment of T2DM in adolescents, including lessons learned from the adult T2DM literature.